Memoryscape : Reconciling Everyday City Dwellers’ Memory with Pretoria’s Heritage Narrative - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2019)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2019.